2018
DOI: 10.1038/s41388-018-0147-x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomas driven by Epstein–Barr virus nuclear antigen-1 (EBNA1) are dependant upon Mdm2

Abstract: Epstein-Barr virus (EBV) associated Burkitt’s lymphoma is characterised by the deregulation of c-Myc expression and a restricted viral gene expression pattern in which the EBV nuclear antigen-1 (EBNA1) is the only viral protein to be consistently expressed. EBNA1 is required for viral genome propagation and segregation during latency. However, it has been much debated whether the protein plays a role in viral-associated tumourigenesis. We show that the lymphomas which arise in EµEBNA1 transgenic mice are unequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…The study reported by Li et al [11] has described p53 as a functionally relevant target of EBV-BHRF1-1 to potentiate lytic replication of EBV in nasopharyngeal carcinoma. Furthermore, several studies have demonstrated that lymphomas driven by EBV are dependent upon MDM2 which can further regulate p53 gene [15,16]. We also found that higher expressions of EBV-BHRF1-1 were associated with lower p53 and p53 protein which can reflect the functional role of p53 gene in our CLL patients.…”
Section: Discussionsupporting
confidence: 63%
“…The study reported by Li et al [11] has described p53 as a functionally relevant target of EBV-BHRF1-1 to potentiate lytic replication of EBV in nasopharyngeal carcinoma. Furthermore, several studies have demonstrated that lymphomas driven by EBV are dependent upon MDM2 which can further regulate p53 gene [15,16]. We also found that higher expressions of EBV-BHRF1-1 were associated with lower p53 and p53 protein which can reflect the functional role of p53 gene in our CLL patients.…”
Section: Discussionsupporting
confidence: 63%
“…Curiously, αDEC-E1 plus Adeno-E1-LMP vaccination led to only a modest increase in EBNA1-specific CD8 + T cells. In recent studies, it was shown that mice with primary BL-E1 tumors had an imbalanced CD4 + /CD8 + T cell ratio in the spleen, which was lower compared with mice without tumors (36). We observed a slight decrease of both CD4 + and CD8 + T cells in tumor-bearing spleens compared with spleens in tumor-free mice, and this was most visible in the PBS-treated mice (Supplemental Figure 4B).…”
Section: Resultssupporting
confidence: 48%
“…However, its host chromatin binding activity also mediates some growth transforming activity 39 . Accordingly, EBNA1 expression in murine B cells induces tumors with some similarities to Burkitt's lymphoma 40 . EBNA2 induces the transcription of the cellular oncogene MYC and compromises lytic EBV replication by inducing Tet methylcytosine dioxygenase 2 (TET2) expression, thereby blocking methylation sites for BZLF1 binding 16,17,41 .…”
Section: Transformation and Oncogenesismentioning
confidence: 99%